2015
DOI: 10.1016/j.bbamcr.2014.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of spike-evoked synaptic transmission: The role of presynaptic calcium and potassium channels

Abstract: Action potentials are usually considered as the smallest unit of neuronal information conveyed by presynaptic neurons to their postsynaptic target. Thus, neuronal signaling in brain circuits is all-or-none or digital. However, recent studies indicate that subthreshold analog variation in presynaptic membrane potential modulates spike-evoked transmission. The informational content of each presynaptic action potential is therefore greater than initially expected. This property constitutes a form of fast activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Evidence suggests that the presynaptic effects of volatile anesthetics on neurotransmitter release are mediated by reduced nerve terminal excitability from inhibition of Na v channels rather than direct inhibition of Ca 2+ influx by inhibition of Ca v channels (7,44,50,51). A critical distinction is between presynaptic reductions in Ca 2+ influx involving direct inhibition of Ca v (e.g., 52) or indirect effects involving alterations in the presynaptic AP waveform as a result of effects on other ion channels including K v and Na v (35,50,51,53). We have previously shown that hippocampal neuron SV exocytosis is much less sensitive to isoflurane when evoked by elevated extracellular KCl to open Ca v rather than by electrical simulation of action potentials (7), which provides further support for a major target upstream of Ca 2+ entry.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the presynaptic effects of volatile anesthetics on neurotransmitter release are mediated by reduced nerve terminal excitability from inhibition of Na v channels rather than direct inhibition of Ca 2+ influx by inhibition of Ca v channels (7,44,50,51). A critical distinction is between presynaptic reductions in Ca 2+ influx involving direct inhibition of Ca v (e.g., 52) or indirect effects involving alterations in the presynaptic AP waveform as a result of effects on other ion channels including K v and Na v (35,50,51,53). We have previously shown that hippocampal neuron SV exocytosis is much less sensitive to isoflurane when evoked by elevated extracellular KCl to open Ca v rather than by electrical simulation of action potentials (7), which provides further support for a major target upstream of Ca 2+ entry.…”
Section: Discussionmentioning
confidence: 99%
“…However, synaptic depolarization also results in Ca 2+ -dependent enhancement of vesicular priming (Awatramani et al, 2005) and exocytosis (Christie et al, 2011) that may deplete the readily releasable pool. Whether these distinct mechanisms act in combination to modify AP-evoked release is unclear (Rama et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In both cases, the principle underlying ADF is that membrane potential fluctuations in the cell body is electrically transmitted by the axon over hundreds of micrometers to the terminals where they modulate the biophysical state of voltage-gated potassium, calcium or sodium channels (Alle and Geiger, 2006; Shu et al, 2006; Christie et al, 2011; Sasaki et al, 2012; Debanne et al, 2013; Rama et al, 2015a,b). Thus, these forms of ADF can be found only in local circuits such as L5-L5 synapses in the cortex or CA3-CA3 synapses in the hippocampus where both the short axonal distance and the limited number of branch-points represent favorable conditions to an optimal transmission of voltage to the presynaptic terminal (Sasaki et al, 2012).…”
Section: Introduction: Digital Analog and Analog-digital Signalingmentioning
confidence: 99%